International consensus statement on robotic pancreatic surgery - Liu, Rong; Hackert, Thilo (Hepatobiliary surgery and nutrition, 2019)
The robotic surgical system has been applied to various types of pancreatic surgery. However, controversies exist regarding a variety of factors including the safety, feasibility, efficacy, and cost-effectiveness of robotic surgery. This study aimed to evaluate the current status of robotic pancreatic surgery and put forth experts’ consensus and recommendations to promote its development. Based on the WHO Handbook for Guideline Development, a Consensus Steering Group and a Consensus Development Group were established to determine the topics, prepare evidence-based documents, and generate recommendations. The GRADE Grid method and Delphi vote were used to formulate the recommendations. A total of 19 topics were analyzed. The first 16 recommendations were generated by GRADE using an evidence-based method (EBM) and focused on the safety, feasibility, indication, techniques, certification of the robotic surgeon, and cost-effectiveness of robotic pancreatic surgery. The remaining three recommendations were based on literature review and expert panel opinion due to insufficient EBM results. Since the current amount of evidence was low/meager as evaluated by the GRADE method, further randomized controlled trials (RCTs) are needed in the future to validate these recommendations.
Gesehen am 09.12.2019